ANALISIS DILATASI WAKTU BERDASARKAN PERSPEKTIF SAINS DAN AL-QUR’AN BERBASIS VIDEO DENGAN MODEL POE2WE - Riza Hasanudin; Nana, Nana; Sulistyaningsih, Dwi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2021)
The purpose of this study is to find out the explanation of time dilation according to scientific theory and the Qur'an, and to analyze the application of video with the POE2WE model. This study uses a qualitative descriptive method with a literature review technique. The results of this study indicate that according to scientific theory time dilation is the time difference due to relative motion. Two observers moving relative to each other will experience a time difference. In several verses of the Qur'an Allah explains that one day according to Allah is equal to a thousand years according to human calculations. This shows that before Einstein discovered the theory of relativity, the Qur'an had long explained the phenomenon. The application of video with the POE2WE model in time dilation physics learning material is very suitable to be applied. The videos are presented in an interesting way so that they are not boring and are not centered on the teacher as a source of information.